Cartilaginous choristoma of the lower lip: report of a case and review of the literature. (28th April 2014) - Halley, D.; Dargue, A.; Pring, M.
Abstract: A choristoma is a tumour‐like mass of histologically normal tissue arising in an ectopic location. A cartilaginous choristoma is a rare finding within the oral cavity and most commonly presents in the tongue. We present an unusual case of a cartilaginous choristoma arising in the lower lip. To our knowledge, this is only the third case reported in the literature to date. The current literature is reviewed and the clinical presentation, differential diagnosis and management of this patient are discussed together with the possible histogenesis.